Social Vulnerability and Premature Cardiovascular Mortality Among US Counties, 2014 to 2018. Issue 16 (19th October 2021) - Khan, Safi U.; Javed, Zulqarnain; Lone, Ahmad N.; Dani, Sourbha S.; Amin, Zahir; Al-Kindi, Sadeer G.; Virani, Salim S.; Sharma, Garima; Blankstein, Ron; Blaha, Michael J.; Cainzos-Achirica, Miguel; Nasir, Khurram
Abstract : Background: Substantial differences exist between United States counties with regards to premature (<65 years of age) cardiovascular disease (CVD) mortality. Whether underlying social vulnerabilities of counties influence premature CVD mortality is uncertain. Methods: In this cross-sectional study (2014–2018), we linked county-level CDC/ATSDR SVI (Centers for Disease Control and Prevention/Agency for Toxic Substances and Disease Registry Social Vulnerability Index) data with county-level CDC WONDER (Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiological Research) mortality data. We calculated scores for overall SVI and its 4 subcomponents (ie, socioeconomic status; household composition and disability; minority status and language; and housing type and transportation) using 15 social attributes. Scores were presented as percentile rankings by county, further classified as quartiles on the basis of their distribution among all US counties (1st [least vulnerable] = 0 to 0.25; 4th [most vulnerable = 0.75 to 1.00]). We grouped age-adjusted mortality rates per 100 000 person-years for overall CVD and its subtypes (ischemic heart disease, stroke, hypertension, and heart failure) for nonelderly (<65 years of age) adults across SVI quartiles. Results: Overall, the age-adjusted CVD mortality rate per 100 000 person-years was 47.0 (ischemic heart disease, 28.3; stroke, 7.9; hypertension, 8.4; and heart failure, 2.4). The largest concentration of counties with more social vulnerabilities and CVD mortality were clustered across the southwestern and southeastern parts of the United States. The age-adjusted CVD mortality rates increased in a stepwise manner from 1st to 4th SVI quartiles. Counties in the 4th SVI quartile had significantly higher mortality for CVD (rate ratio, 1.84 [95% CI, 1.43–2.36]), ischemic heart disease (1.52 [1.09–2.13]), stroke (2.03 [1.12–3.70]), hypertension (2.71 [1.54–4.75]), and heart failure (3.38 [1.32–8.61]) than those in the 1st SVI quartile. The relative risks varied considerably by demographic characteristics. For example, among all ethnicities/races, non-Hispanic Black adults in the 4th SVI quartile versus the 1st SVI quartile exclusively had significantly higher relative risks of stroke (1.65 [1.07–2.54]) and heart failure (2.42 [1.29–4.55]) mortality. Rural counties with more social vulnerabilities had 2- to 5-fold higher mortality attributable to CVD and subtypes. Conclusions: In this analysis, US counties with more social vulnerabilities had higher premature CVD mortality, varied by demographic characteristics and rurality. Focused public health interventions should address the socioeconomic disparities faced by underserved communities to curb the growing burden of premature CVD. Abstract : Supplemental Digital Content is available in the text.